The self‐compatibility effect in graded thermoelectric cooler elements. Issue 7 (10th April 2013) - Seifert, Wolfgang; Snyder, G. Jeffrey; Toberer, Eric S.; Goupil, Christophe; Zabrocki, Knud; Müller, Eckhard
<x xml:space="preserve">Abstract</x> The compatibility approach enables the description of thermoelectric (TE) effects in terms of intensive state variables. Based on the new concept of a "Thomson cooler" (using the particular case of a u = s cooler as a demonstration) the authors present practically relevant results about fully self‐compatible cooler elements where the compatibility factor s is adjusted locally at any position along the element. By means of a comparison u = s cooler vs. conventional Peltier cooler with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg277v2j83" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(Bi0.5Sb0.5)2Te3</alternatives> material it is shown that there is a similar self‐compatibility effect for different ΔT. Therewith, the paper completes results published in Phys. Rev. B 86, 045202 (2012).